2016
DOI: 10.1016/j.nantod.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal (Fe, Co, Ni, and Mn) oxides for oxygen reduction and evolution bifunctional catalysts in alkaline media

Abstract: In recent years, a large amount of focus has been given to the development of alternative energy sources that are clean and efficient; among these, electrochemical energy holds potential for its compatibility with solar and wind energy, as well as its applications in metal-metal and metal-air batteries. However, these technologies require the use of a catalyst to make this application feasible. Current catalysts consist of precious metals such as platinum, which are expensive and block common access to electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
453
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 836 publications
(459 citation statements)
references
References 125 publications
(102 reference statements)
4
453
0
2
Order By: Relevance
“…Thus, spinel and perovskite structure with multi-metal components are largely used for ORR and OER catalysis. [32] Spinel oxides (A x B 3−x O 4 ) can be used as bifunctional ORR/OER catalyst in alkaline media. [46] Among spinel oxides, the electron transfer occur with quite low activation energy between the cations of different valences.…”
Section: Mixed-metal Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, spinel and perovskite structure with multi-metal components are largely used for ORR and OER catalysis. [32] Spinel oxides (A x B 3−x O 4 ) can be used as bifunctional ORR/OER catalyst in alkaline media. [46] Among spinel oxides, the electron transfer occur with quite low activation energy between the cations of different valences.…”
Section: Mixed-metal Engineeringmentioning
confidence: 99%
“…[32] Thus, the formation of RuO 2 /MnO 2 composite is promising for bifunctional ORR/OER. For example, Sun et al reported the synthesis of RuO 2 nanoparticles supported on MnO 2 nanorods (np-RuO 2 /nr-MnO 2 ) via a two-step hydrothermal reaction.…”
Section: 1 Metal Oxide/metal Oxidementioning
confidence: 99%
“…Besides, these metals can easily change from one oxidation state to another therefore it gives them the ability to tolerate the unchanging reduction and oxidation reactions which take place inside an electrolytic cell, thus improving stability [26,77]. Due to their natural activities, adequate stability in oxidative electrochemical environments, their structural multiplicity, as well as their ability to be mixed, doped, and to be fused with other materials such as carbon and graphene; transition metals and their oxides are regarded as promising way of enhancing AC catalytic activity [26,78]. Various transition metals like cobalt [27,79], manganese [29,77], nickel [80] and iron, have been mostly used as AC dopant for catalysis of oxygen reduction reaction (ORR) among a wide range of these metals.…”
Section: Transition Metal/oxides Dopingmentioning
confidence: 99%
“…The same array of ORR catalytic activity performance for these metals was observed which is consistent with the order of their active sites contents, fortunately Fe is the most abundant metal on earth which makes it a good candidate for this application. However, Fe when used in acidic media suffer from a lower catalytic activity, and from stability issues [26].…”
Section: Transition Metal/oxides Dopingmentioning
confidence: 99%
See 1 more Smart Citation